Determinants of foreign direct investment and foreign direct investment in agriculture in developing countries - Farr, Fabian (Kansas State University, 2017)
Understanding determinants of Foreign Direct Investment (FDI) and Agricultural Foreign Direct Investment (AGFDI) is vital to policy makers in developing countries. FDI is a source of capital for the host country that does not affect its debt balance. Even so, technological spillover, better infrastructure as well as an increase in value added and market access have been the source of motivation to increase efforts to attract FDI. As for AGFDI, ongoing uncertainty with the financial markets created a shift in private investment towards tangible assets, which favors AGFDI to developing countries. Nevertheless, investment in agriculture suffers from low commodity prices and increasing productivity loss that discourage FDI and AGFDI. Therefore, it is crucial for policy makers to understand the determinants of AGFDI to create an attractive environment for potential investors. We use country level panel data to estimate the impacts of country-level economic and social variables on FDI and AGFDI. The data consist of 22 developing countries. A subsample of 13 Latin American countries is also studied. Country and year fixed effects are used to isolate the impacts of the explanatory variables on FDI and AGFDI. The explanatory variables wer constructed to avoid contemporaneous endogeneity. FDI determinants are consistent with previous studies and confirm traditional variables such as economy size, infrastructure and trade openness encourage FDI. A new variable that measures energy imports as a share of total energy use was negative for both main samples of FDI. The results of the Latin American panel for AGFDI, were mostly consistent with FDI determinants. Infrastructure, energy imports and economy size, as well as forestland share and agricultural value-add were statistically significant for the amount of investment inflow and total flow respectively. Further analysis with larger samples is necessary to confirm findings. Also, social and environmental impacts of AGFDI should be included in future studies.
Keywords: Foreign Direct Investment; Agriculture products; Developing countries